POLYSOMNOGRAPHIC CHARACTERISTICS AND CPAP TREATMENT OUTCOME OF OBSTRUCTIVE SLEEP APNAE PATIENTS IN MONGOLIA - Shuren D, D.; Damdindorj , B.; Otgonbayar , L. (EurasianUnionScientists, 2020)
Obstructive sleep apnea (OSA) is a syndrome of recurrent, partial, or complete upper airway collapse during sleep. These events often result in reductions in blood oxygen saturation and usually terminates by brief arousals from the sleep. Shortness of breath during sleep is a result of weakening of the airway muscles, narrowing of the pharyngeal wall and the upper respiratory tract at the level of the nasopharynx. (1) The first symptom of NAP is drowsiness during the day, resulting in diminished attention and drowsiness. In addition, complications such as heart attack, low blood pressure??, respiratory and cardiovascular failure, high blood pressure, and cardiac arrhythmias are common